2014
DOI: 10.2139/ssrn.2580599
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Country-Heterogeneous and Time-Varying Effects of Unconventional Monetary Policies in AEs on Portfolio Inflows to EMEs

Abstract: This paper examines crosscountry heterogeneity and time-variability in the effects of unconventional monetary policies (UMPs) in advanced economies (AEs) on portfolio inflows to emerging economies (EMEs), with a panel smooth transition regression model. The drivers of the two dimensional nonlinearities are country-specific factors such as the current account, real effective exchange rate deviation from its historical average, and foreign exchange reserves. The elasticity of portfolio inflows to EMEs with respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Koepke (2018), reveals that both factors are vital in effecting the level of bond flows in EMEs where factors such as inclusion in stock index and United States of America (US) monetary policy expectations should be taken into consideration in examining the drivers of bond flows in EMEs. In addition, (Ahmed et al, 2017;Ghosh et al, 2014;Horioka et al, 2016;Mishra et al, 2014;Moore et al, 2013;Punzi & Chantapacdepong, 2017;Yoon & Hurlin, 2014) found that the capital inflows into EMEs can be associated with strong macroeconomic fundamentals of the country such as strong GDP growth, deeper financial markets, lower current account deficit and higher government bond https://doi. org/10.15405/epsbs.2020.10.8 Corresponding Author: Hock-Ann Lee Selection and peer-review under responsibility of the Organizing Committee of the conference eISSN: 2357-1330 91 yields.…”
Section: Problem Statementmentioning
confidence: 99%
“…Koepke (2018), reveals that both factors are vital in effecting the level of bond flows in EMEs where factors such as inclusion in stock index and United States of America (US) monetary policy expectations should be taken into consideration in examining the drivers of bond flows in EMEs. In addition, (Ahmed et al, 2017;Ghosh et al, 2014;Horioka et al, 2016;Mishra et al, 2014;Moore et al, 2013;Punzi & Chantapacdepong, 2017;Yoon & Hurlin, 2014) found that the capital inflows into EMEs can be associated with strong macroeconomic fundamentals of the country such as strong GDP growth, deeper financial markets, lower current account deficit and higher government bond https://doi. org/10.15405/epsbs.2020.10.8 Corresponding Author: Hock-Ann Lee Selection and peer-review under responsibility of the Organizing Committee of the conference eISSN: 2357-1330 91 yields.…”
Section: Problem Statementmentioning
confidence: 99%